Is the Management of Rectal Cancer Using a Watch and Wait Approach Feasible, Safe and Effective in a Publicly Funded General Hospital?. Issue 1 (January 2022) - Kaul, S.; Rao, C.; Mane, R.; Tan, K.L.; Khan, A.H.A.; Hussain, M.S.; Shafi, M.A.; Buettner, F.; Banerjee, S.; Boulton, R.; Bhargava, A.; Huang, J.; et al.
Abstract: Aims: Although there is emerging evidence to suggest equivalent oncological outcomes using a watch and wait approach compared with primary total mesorectal excision surgery, there is a paucity of evidence about the safety and efficacy of this approach in routine clinical practice. Here we report the long-term outcomes and quality of life from patients managed with watch and wait following a clinical complete response (cCR) to neoadjuvant therapy. Materials and methods: Patients with adenocarcinoma of the rectum with cCR following neoadjuvant therapy managed using watch and wait were retrospectively identified. Demographic data, performance status, pretreatment staging information, oncological and surgical outcomes were obtained from routinely collected clinical data. Quality of life was measured by trained clinicians during telephone interviews. Results: Over a 7-year period, 506 patients were treated for rectal cancer, 276 had neoadjuvant therapy and 72 had a cCR (26.1%). Sixty-three were managed with watch and wait. Thirteen patients had mucosal regrowth. There was no significant difference in the incidence of metastatic disease between the surgical and watch and wait cohorts ( P = 0.38). The 13 patients with mucosal regrowth underwent salvage surgery. Eleven of the patients who underwent surgical resection had R0 resections. There was also a statistically and clinically significant improvement in the Functional Assessment of Cancer Therapy – Colorectal (FACT-C) trial outcome index ( P = 0.022). Conclusion: This study shows that watch and wait is safe and effective outside of tertiary referral centres. It suggests that an opportunistic cCR is durable and when mucosal regrowth occurs it can be salvaged. Finally, we have shown that quality of life is probably improved if a watch and wait approach is adopted. Highlights: This study reports high clinical complete response rate (cCR) (26.1%). It reports high pathological complete response rate (77.8%) following cCR. All patients with mucosal regrowth underwent salvage surgery with R0 resection rate of 84.6%. There was no difference in APER rate compared to the primary surgical cohort. It demonstrates equivalent survival and improved sphincter preservation with watch-and-wait (WW). This study is one of the first comparative reports of quality-of-life following WW and surgery. It shows that colorectal specific quality-of life (p = 0.0008) and FACT-C TOI (p = 0.022) is better with WW.